2009
DOI: 10.1074/mcp.m900211-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Enrichment and Characterization of Mucin Core-1 Type Glycopeptides from Bovine Serum

Abstract: The lack of consensus sequence, common core structure, and universal endoglycosidase for the release of O-linked oligosaccharides makes O-glycosylation more difficult to tackle than N-glycosylation. Structural elucidation by mass spectrometry is usually inconclusive as the CID spectra of most glycopeptides are dominated by carbohydrate-related fragments, preventing peptide identification. In addition, O-linked structures also undergo a gas-phase rearrangement reaction, which eliminates the sugar without leavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
116
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 53 publications
8
116
1
4
Order By: Relevance
“…Clustered O-glycans significantly increase the m/z of precursor cations, thus lowering the charge density. The consistent requirement for supplemental activation in our current and previous studies (20,22) of IgA1 O-glycopeptides corroborates broader observations on its use to disrupt non-covalent interactions after ECD/ETD and increase the fragmentation efficiency of higher charge state precursor cations (45,47). Several groups have also reported the use of different proteases to change the relative location of the charge within peptides to optimize ECD/ETD peptide fragmentation (44,48).…”
Section: Application Of Ecd/etd To Clustered Sites Of O-glycosylationsupporting
confidence: 90%
See 1 more Smart Citation
“…Clustered O-glycans significantly increase the m/z of precursor cations, thus lowering the charge density. The consistent requirement for supplemental activation in our current and previous studies (20,22) of IgA1 O-glycopeptides corroborates broader observations on its use to disrupt non-covalent interactions after ECD/ETD and increase the fragmentation efficiency of higher charge state precursor cations (45,47). Several groups have also reported the use of different proteases to change the relative location of the charge within peptides to optimize ECD/ETD peptide fragmentation (44,48).…”
Section: Application Of Ecd/etd To Clustered Sites Of O-glycosylationsupporting
confidence: 90%
“…Broader studies on peptide and glycopeptide ETD fragmentation have indicated that peptide charge density (residues per charge) plays a significant role in the amount of backbone fragmentation (45,46). The difference in observed fragments for the 3 ϩ and 4…”
Section: Application Of Ecd/etd To Clustered Sites Of O-glycosylationmentioning
confidence: 99%
“…Additionally, the exact glycosylation site of identified peptides containing several Ser/Thr residues cannot be predicted due to the lack of a consensus sequence for mucin-type O-glycosylation. The alternative fragmentation techniques electron capture dissociation (ECD) (38,39) and electron transfer dissociation (ETD) (40) have been introduced for site-specific analysis of CID-labile PTMs but characterization of protein O-glycosylations using ECD/ETD have generally been limited to synthetic glycopeptides or single glycoproteins (41)(42)(43)(44)(45) (46). We have previously developed a sialic acid specific capture-and-release protocol for the enrichment of both N-and O-glycosylated peptides from sialylated glycoproteins in biological samples using hydrazide chemistry (37).…”
mentioning
confidence: 99%
“…Furthermore, even HCD-MS/MS begins to lose its usefulness when the number of saccharide residues exceeds ϳ4 -5 (whether in a single glycan or spread out among multiple sites), reverting again to domination by sugar losses and lack of peptide fragmentation at reasonable collision energies (5,12). This situation is alleviated partly by the use of electron capture dissociation/ETD-MS/MS, which provides peptide sequence ions with substantial retention of the glycan, making its site known in a relatively uncomplicated way.…”
mentioning
confidence: 99%
“…However, even electron capture dissociation/ETD-MS/MS has its limitations, with heavy glycosylation and/or a lack of abundant precursors with required multiple charge states (e.g. ϩ3, ϩ4, and ϩ5) being two typical reasons for failure to observe sufficient fragmentation for site-specific sequence analysis (5,12,13). The limitations can become acute when there are many adjacent Ser and Thr residues with potential for glycosylation and many Pro residues interrupting the continuity of c/z fragmentation, both situations being frequent in O-glycosylated peptides.…”
mentioning
confidence: 99%